1996
DOI: 10.1071/ch9960475
|View full text |Cite
|
Sign up to set email alerts
|

Novel Uperin Peptides From the Dorsal Glands of the Australian Floodplain Toadlet Uperoleia inundata

Abstract: The dorsal glandular extract of the floodplain toadlet Uperoleia inundata contains more than 50 peptides: we report the amino acid sequences and bioactivity data of 13 of these. The peptides have been sequenced by using a combination of mass spectrometry and automated Edman sequencing. Ten of the peptides have been synthesized in order to confirm their structures, and to enable bioassays to be carried out. Ten peptides are host- defence agents, including ( i ) a powerful new neuropeptide of the tachykinin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It is one of the most potent membrane-active antibiotic peptides isolated from amphibians and is particularly effective against Gram-positive organisms [8]. Citropin 1.1 is a 16 residue peptide and is one of a number of amphibian antibiotic peptides containing the characteristic Lys7-Lys8 pattern: a group which includes lesueurin (from L. lesueuri) [17], the aureins (from L. aurea and L. raniformis) [11] and the uperins (from toadlets of the genus Uperoleia) [68]. Citropin 1.1 does not cause lysis of red blood cells at a concentration of 100 lgAEmL )1 , but lysis is complete at 1 mgAEmL )1 (B. C. S. Chia & J. H. Bowie, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most potent membrane-active antibiotic peptides isolated from amphibians and is particularly effective against Gram-positive organisms [8]. Citropin 1.1 is a 16 residue peptide and is one of a number of amphibian antibiotic peptides containing the characteristic Lys7-Lys8 pattern: a group which includes lesueurin (from L. lesueuri) [17], the aureins (from L. aurea and L. raniformis) [11] and the uperins (from toadlets of the genus Uperoleia) [68]. Citropin 1.1 does not cause lysis of red blood cells at a concentration of 100 lgAEmL )1 , but lysis is complete at 1 mgAEmL )1 (B. C. S. Chia & J. H. Bowie, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Group II has only one member, Da-1039 (Fig. 6B), with only very limited homology to the uperin family of antibacterial frog skin secretions (Bradford et al, 1996;Steinborner et al, 1997). Group III comprise three 9e11 residue Dq toxins with moderate homology with the temporin family of antibacterial frog skin secretions (Abbassi et al, 2008;Rinaldi and Conlon, 2013;Simmaco et al, 1996).…”
Section: Dinoponeratoxinsmentioning
confidence: 99%
“…5). A family of structurally related peptides, termed the uperins, has been isolated from the Australian frogs Uperoleia mjoberii [51] and Uperoleia inundata [52] that are active against Gram-positive bacteria. From the species Crinia signifera, two peptides differing by a single amino acid, termed signiferin 2.1 and signiferin 2.2, were identified that are also active against Gram-positive bacteria [53].…”
Section: Myobatrachidaementioning
confidence: 99%